Hubungan Kelekatan Ayah dengan Regulasi Emosi pada Wanita Dewasa Awal yang Bekerja dan Belum Menikah - Angri Novita Dewi; Ambarwati, Krismi Diah (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
In facing the developmental tasks of early adulthood, good emotional regulation is required in order to effectively manage emotions while dealing with various demands. Especially among young adult women, as young adult women tend to have more demands in early adulthood compared to young adult men. The demands of these developmental tasks are best faced by having good emotional regulation in order to avoid psychological issues while fulfilling developmental tasks. The objective of this research is to examine the relationship between father attachment and emotional regulation in young adult women The research method employed is quantitative with a correlational design. The research included 213 participants, specifically young adult women aged 18-25 years, who were unmarried and employed, selected through incidental sampling method. The scale used to measure father attachment is the Inventory of Parent and Peer Attachment (IPPA), and the scale used to measure emotional regulation is the Cognitive Emotion Regulation Questionnaire (CERQ). The data analysis method employed was Spearman's Rho. The research results indicate a significant positive relationship between father attachment and emotional regulation in young adult women (r= 0,285 and sig.=0,000). The more secure the attachment between fathers and young adult women, the higher the emotional regulation they possess. Thus, the hypothesis in this research is accepted. It is hoped that young adult women can continue to develop emotional regulation effectively to cope with the demands of early adulthood and prevent the emergence of issues during this developmental stage.